Strengthening Elementary Students’ Reading Skills through Metacognitive Strategies: Insights from a Systematic Review - Teguh Prasetyo; Rasmitadila Rasmitadila; Rachmah Amalia (Universitas Pendidikan Ganesha, 2025)
Reading literacy in elementary school is a fundamental competency that often faces challenges in text comprehension, learning independence, and student motivation. This study aims to analyze and evaluate the strategies and effectiveness of implementing metacognitive approaches in elementary school reading instruction through a systematic literature review. Literature was retrieved from ERIC, Google Scholar, Crossref, and OpenAlex databases, with inclusion criteria: primary research articles addressing metacognitive approaches in elementary reading instruction, published in Scopus or SINTA indexed journals, and dated between 2020–2025. The literature selection process followed the PRISMA framework, including identification, screening, eligibility, and inclusion stages. Data were thematically analyzed to identify patterns of metacognitive strategies and their impacts on reading skills, comprehension, learning independence, and student motivation. The review findings indicate that metacognitive approaches, encompassing planning, monitoring, and evaluation stages, consistently enhance reading skills and foster students as reflective and independent learners. These results highlight the importance of integrating metacognitive strategies into reading instruction, while providing guidance for teacher training programs and the use of educational technology to tailor learning experiences to students’ diverse needs. The study’s implications support the enhancement of critical literacy, higher order thinking skills, and learning autonomy from the elementary level.